Pengaruh Corporate Social Responsibility dan Tax Planning terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Variabel Moderasi - Sri Ayem; Yulita Hanasari Putri (Universitas Batanghari Jambi, 2023)
This research aims to find out the effect of corporate social responsibility and tax planning to firm value with institutional ownership as a moderating variable. Sample in this research is the firm of mining which enlist in Indonesia stock exchange from periode 2015 to 2019. The data analysis used is regression analysis moderation. Regression results show that csr,tax planning, and institutional ownership are influencing the firm value are not.